1980
DOI: 10.1037/0033-2909.88.2.429
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of research on psychotherapy outcome with adolescents: 1967–1977.

Abstract: This article provides a critical review of research on psychotherapy outcome with adolescents. Studies on individual, group, and family therapy that were published largely from 1967 through 1977 are described and critically evaluated. Of 33 independent investigations, 5 are judged as exemplary in methodological scope and rigor. Although methodological deficiencies abound, the greater weight of available evidence on adolescents does point toward the superiority of psychotherapy over no-therapy conditions, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The reference sections of previous reviews, m n t relevant public@ions, and articles identified in the computer search were examined for studies which coul~d be included in the analysis (e.g., Casey & Berman, 1985;Dagley, et. al, 1994;Dies & Riester, 1986;Sugar, 1993;Tramonta, 1980;Weisz et al, 1987). Initially, well over 100 studies were identified for possible inclusion in this study.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The reference sections of previous reviews, m n t relevant public@ions, and articles identified in the computer search were examined for studies which coul~d be included in the analysis (e.g., Casey & Berman, 1985;Dagley, et. al, 1994;Dies & Riester, 1986;Sugar, 1993;Tramonta, 1980;Weisz et al, 1987). Initially, well over 100 studies were identified for possible inclusion in this study.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…et al, 1978;Dagley et al, 1994;Dies & Riester, 1986;Kazdin, 1991;Sugar, 1993;Tramonta, 1980), both in quantity of studies and quality or sophistication of its methodology @agley et Kazdin, Bass, Ayers, & Rogers, 1990). This mela-analysis, based on 20 years of outcome literature, produced only 56 rateable outcome studbs.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Eysenck's challenge in 1952 is quoted by several authors (Eysenck, 1985;Hibbs, 2001;Kazdin, 1978;Tramontana, 1980). He reviewed the literature on the effi cacy of psychotherapy and concluded that psychotherapy made no impact on the process of spontaneous remission (Eysenck, 1952(Eysenck, /1973.…”
Section: Chronological Review Of the Literature (I) Establishment Of mentioning
confidence: 99%
“…As more research emerged, Eysenck's original work was reassessed. Two researchers reanalysed Eysenck's fi rst study and criticized it for overestimating the recovery rate in the untreated group (Tramontana, 1980). Yet the critics were not completely silenced.…”
Section: Chronological Review Of the Literature (I) Establishment Of mentioning
confidence: 99%
“…For decades thereafter, the literature was dominated by rebuttals, new reviews, and re-reviews. An excellent picture of the progress in the field can be obtained by a serial reading of critical articles following Levitt's (1957) challenge, including, Heinicke and Goldman (1960), Hood-Williams (1960), Eisenberg and Gruenberg (1961), Levitt (1963), Heinicke and Strassmann (1975), Hartmann, Roper, and Gelfand (1977), Barrett, Hampe, & Miller (1978), Tramontana (1980), Casey and Berman (1985), Weisz, Weiss, Alicke, and Klotz (1987), Kazdin, Bass, Ayers, & Rodgers (1990), Kazdin (1991), Mann and Borduin (1991), and Kazdin (1993). More restricted reviews of specific interventions are presented by Urbain and Kendall (1980), Ollendick (1986), Kovacs and Paulauskas (1986), Hazelrigg, Cooper, and Borduin (1987), Werry and Wollersheim (1989), Barrnett, Docherty, and Frommelt (1991), Durlak, Fuhrman, andLampman (1991), andKenclall (1993).…”
Section: Dimenslons Of Progress Over Four Decadesmentioning
confidence: 99%